Analysis of the morphometric variations in natural fibres by automated laser scanning: Towards an efficient and reliable assessment of the cross-sectional area. (May 2018) - Garat, William; Corn, Stephane; Le Moigne, Nicolas; Beaugrand, Johnny; Bergeret, Anne
Abstract: The development of natural fibres in engineering applications requires the reliable and accurate assessment of their dimensional characteristics and mechanical properties. Fibre cross-sectional area (CSA) obtained from lateral dimensional measurements should consider the specific cross-sectional shape of natural fibres and its wide lengthwise morphometric variations. In this study, a detailed dimensional analysis was conducted on a selected panel of natural fibres with contrasted morphometric characteristics belonging to various phylogenetic plant species with dissimilar functions in planta . An automated laser scanning technique was used, and geometrical models and filtering data method were developed for calculation of reliable CSAs adapted to each plant fibre species. Results show that CSAs of palm and sisal fibre bundles can be satisfactorily assessed by a circular model with minimal data processing, whereas hemp, flax and nettle fibre bundles require specific data filtering due to partial splicing, and can be better assessed by an elliptic model.